Recent Advances of Radionuclide-Based Molecular Imaging of Atherosclerosis - M. Kazuma, Soraya; Sultan, Deborah; Zhao, Yongfeng; Detering, Lisa; You, Meng; P. Luehmann, Hannah; S.P. Abdalla, Dulcineia; Liu, Yongjian (Current Pharmaceutical Design, 2015)
Atherosclerosis is a systemic disease characterized by the development of multifocal plaque lesions within vessel walls and extending into the vascular lumen. The disease takes decades to develop symptomatic lesions, affording opportunities for accurate detection of plaque progression, analysis of risk factors responsible for clinical events, and planning personalized treatment. Of the available molecular imaging modalities, radionuclidebased imaging strategies have been favored due to their sensitivity, quantitative detection and pathways for translational research. This review summarizes recent advances of radiolabeled small molecules, peptides, antibodies and nanoparticles for atherosclerotic plaque imaging during disease progression.
Keywords: PET